2015
DOI: 10.1016/j.envres.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A exposure and behavioral problems among inner city children at 7–9 years of age

Abstract: Background Bisphenol A (BPA) is a ubiquitous endocrine disrupting compound. Several experimental and epidemiological studies suggest that gestational BPA exposure can lead to neurodevelopmental and behavioral problems in early-life, but results have been inconsistent. We previously reported that prenatal BPA exposure may affect child behavior and differently among boys and girls at ages 3-5 years. Objectives We investigated the association of prenatal and early childhood BPA exposure with behavioral outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
105
4
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 60 publications
(90 reference statements)
12
105
4
2
Order By: Relevance
“…Consistent with this idea, Braun et al (2009Braun et al ( , 2011 observed that gestational BPA exposure is associated with anxious and depressive behaviors, as well as altered executive function, especially in girls. However, the direction of change and magnitude of BPA effects on boys and girls differ among several epidemiological studies (Harley et al, 2013;Palanza et al, 2008;Perera et al, 2012;Roen et al, 2015). This may depend on the timing of the exposure (Roen et al, 2015).…”
Section: Effects On 5α-r Isozymesmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistent with this idea, Braun et al (2009Braun et al ( , 2011 observed that gestational BPA exposure is associated with anxious and depressive behaviors, as well as altered executive function, especially in girls. However, the direction of change and magnitude of BPA effects on boys and girls differ among several epidemiological studies (Harley et al, 2013;Palanza et al, 2008;Perera et al, 2012;Roen et al, 2015). This may depend on the timing of the exposure (Roen et al, 2015).…”
Section: Effects On 5α-r Isozymesmentioning
confidence: 96%
“…Early-life BPA exposure interferes with brain sexual dimorphism, normal neocortical development and synapse formation (Wolstenholme et al, 2011). In addition to animal studies (Palanza et al, 2008), epidemiological evidences suggest that childhood behavioral, emotional, and learning development might be altered in human by BPA (Braun et al, 2009(Braun et al, , 2011Harley et al, 2013;Perera et al, 2012;Roen et al, 2015). As a consequence, the US National Toxicology Program (NTP) expressed in 2008 some concern about the potential effects of BPA on the brain and behavior of fetuses, infants and children at current human exposures to it.…”
Section: Introductionmentioning
confidence: 98%
“…A study by Roen et al (2015) investigated the association between prenatal and early childhood BPA exposure and the subsequent behavioral outcomes in 7-9-year-old minority children (n=250). Both boys and girls were affected, but the direction of the associations differed between boys and girls.…”
Section: Bisphenol Amentioning
confidence: 99%
“…Emerging data suggest a potent effect of developmental http://dx.doi.org/10.1016/j.chemosphere.2015.06.061 0045-6535/Ó 2015 Elsevier Ltd. All rights reserved. exposure to BPA on neurogenesis and myelination processes (Tiwari et al, 2014a,b), brain organization, and behavior (Roen et al, 2015;Wolstenholme et al, 2011). BPA might also contribute to the incidence of other mental disorders such as attention deficit hyperactivity disorder (ADHD) (Harley et al, 2013) and schizophrenia (Brown, 2009).…”
Section: Introductionmentioning
confidence: 98%